Detection of Epstein-Barr Virus in Saliva and Gen LMP1 among HIVInfected Patients - Munthe, Eliza Kristina M; Wisaksana, Rudi; Amalia, Riezki; Sufiawati, Irna (UI Scholars Hub, 2019)
Epstein-Barr virus (EBV) is also called human herpes virus 4 (HHV-4), has detected 95% of the population and shows an asymptomatic state. EBV is etiological agent of oral hairy leukoplakia (OHL) in HIV patients. Latent membrane protein 1 (LMP1), an integral EBV protein can modulate growth, differentiation, induce the expression of several cells, activation of antigens, and adhesion molecules. The LMP1 gene has been associated with OHL. Objectives: to determine the prevalence of EBV in saliva and the LMP1 gene in HIV/AIDS patients with EBV positive. Methods: A cross-sectional was conducted on HIV/AIDS patients. The presence of EBV in saliva was done by mciroarray PCR. LMP1 is examined by using nested PCR. Results: The research subjects involved 30 HIV/AIDS patients consisting 70% men and 30% women, with 50 % age group of 31-40 years old and 40% had CD4 counts <200 cells/mm3 (40%). EBV in saliva was found in 26 out of 30 (87%) HIV patients and LMP1 was detected in 17 patients (65.38%). Conclusion: The high prevalence of EBV in saliva and the LMP1 gene may increase the risk of OHL. Early screening for EBV infection in patients with HIV/AIDS is important to reduce the risk of EBV-associated diseases.